The Inheritance - Phillips, Michael R. 1946- (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2016)
"Despite her business success in Washington, DC, a woman troubled by questions about her roots and identity receives a surprising letter from a solicitor's firm; meanwhile, the death of a clan patriarch in Scotland's Shetland Islands paralyzes the economy of an entire community"--
Keywords: Inheritance and succession -- Fiction; Orphans -- Fiction; Scotland -- Fiction; Christian fiction